Snapshots in time: quantifying dynamics of coastal vessel traffic in a dolphin hotspot - William Carome; William Rayment; Elisabeth Slooten; M. Hamish Bowman; Emmanuelle Martinez; Stephen M. Dawson (New Zealand Journal of Marine and Freshwater Research, 2024)
Small vessels contribute substantially to coastal soundscapes, presenting myriad potential impacts on marine species and ecosystems, yet are challenging to monitor using standard tracking methods (e.g. AIS). Here, we present an automated camera system developed to quantify coastal vessel traffic in a core habitat for Hector's dolphins ( Cephalorhynchus hectori ) within Akaroa Harbour, Aotearoa New Zealand. Analysis of 55,569 images taken during the austral summer of 2019/20 showed that traffic was highest around midday, on weekends, and in January. A mean of 41.9 vessel trips per day transited the area of core habitat. Vessel speeds estimated from photographs were assigned to 5‐knot bins with 84% accuracy. Findings suggest vessel traffic in Akaroa Harbour has approximately doubled between 2006–2008 and 2020. Additionally, tours focused specifically on dolphins composed a significantly larger proportion of vessel traffic in 2020 than observed during 2006–2008. We validate the use of an automated camera system as a robust, novel, repeatable, and cost‐effective tool for quantifying fluctuations in coastal vessel traffic. Such tools can provide baseline data and help assess impacts, and their use can guide management action.